RELASI KUASA DALAM PERKAWINAN ANAK (Studi di Kecamatan Greged Kabupaten Cirebon) - Fitriana Fitriana; Siti Fatimah (INKLUSIF (JURNAL PENGKAJIAN PENELITIAN SYARIAH DAN ILMU HUKUM), 2023)
ABSTRACTFITRIANA. 19086040003. "RELATIONS OF POWER IN CHILD MARRIAGE (Case Study in Greged District, Cirebon Regency)", 2022.Child marriage is still one of the phenomena that worries the world and often makes teenagers make it their main goal in life. Not least the cause of child marriage is the existence of power relations. Based on absolute numbers, the highest number of child marriages was found on the island of Java, which then made the authors study Cirebon Regency. This is reinforced by reports recorded at the Sumber Religious Court, that as many as 1,640 marriage dispensation applications were registered from 2018 to June 2022, and Greged District is one of the Districts with the highest marriage rate in Cirebon Regency. This paper discusses the contextual conditions of the prevalence of child marriage in Greged District, what factors have caused the rise of child marriage, and what are the impacts on women there. The theory that the writer uses as a knife for this analysis is Michel Foucault's Power Relations theory. The essence of Foucault's thought is power and knowledge. The method used is a qualitative research method with a legal sociology approach. The results of this study are first, the highest child marriage rate is occupied by Lebak Mekar Village and the lowest is occupied by Greged Village. This sub-district is dominated by farm laborers as well as traders, 100% Muslim and safe political conditions. Second, low educational strata, limited finances, existence of power relations, traditional assumptions, juvenile delinquency problems, and religious understanding are the factors causing the rise of child marriage. Third, the impact on women is health risk, cut off from education, increasing poverty for women, and the potential to experience domestic violence.Keywords: Child Marriage, Power Relations, Greged